Data transferring model determination in robotic group - Hernández Perdomo, W. (2017)
This paper describes the basic idea of data transferring in the group of robots while they move in an area with a high density of obstacles with the goal of increasing their movement speed by creating and synchronizing an area map that is made by each robot separately. This paper provides a brief review of existing robotic swarm projects and definition of the problems in robot teamwork, shows pathfinding methods and their analysis, justifies our technical vision system choice and describes its method of obstacle detecting that is based on dynamic triangulation. According to some behavioristic models, using fuzzy logic, the method of leader changing was used. This knowledge helps with the choice of appropriate models of data transferring, makes their simulation and creates a proper network between the robots to avoid data loss.